Ectopic acromegaly with tumoral range hyperprolactinemia and apoplexy with a dramatic regression of pituitary hyperplasia - Gupta, Ashish; Kasaliwal, Rajeev; Das, Liza; Sharma, Surendra Kumar; Kaur, Vaishali; Vasiljevic, Alexandre; Raverot, Véronique; Korbonits, Márta; Dutta, Pinaki (Frontiers in Endocrinology, 2024)
Acromegaly due to ectopic secretion of growth hormone-releasing hormone (GHRH) is a rare disorder. The signs and symptoms of ectopic acromegaly are indistinguishable from acromegaly due to a somatotroph adenoma. A 35-year-old female presented with secondary amenorrhea for 10 years, intermittent headache, and reduced vision in both eyes for 4 years, which worsened over 4 months before presentation. Additionally, she was diagnosed with uncontrolled diabetes mellitus. On examination, she had coarse facial features, a fleshy nose, and acral enlargement. She had diminished visual acuity (left>right) and bitemporal hemianopia on perimetry. Biochemical investigations revealed elevated IGF-1 [588 ng/ml, reference range (RR) 100–242], markedly elevated basal growth hormone (>80 ng/ml; RR, 0.12–9.88), and hyperprolactinemia in the tumoral range (832 ng/ml; RR, 5–25). MRI sella demonstrated a 22×30×34mm sellar-suprasellar mass with T2 hypointensity. Chest imaging revealed a 75×87×106mm left lung mass, which was found to be a well-differentiated neuroendocrine tumor (NET) on biopsy. Plasma GHRH levels were elevated [38,088 ng/l; RR, <250–300], and a diagnosis of ectopic acromegaly secondary to lung neuroendocrine tumor was considered. During workup, the patient developed in-hospital pituitary apoplexy, which improved with medical management. After a left pneumonectomy, her clinical features of acromegaly improved, her diabetes underwent remission, and there was a marked reduction in plasma GHRH and pituitary size. Histopathology was suggestive of a neuroendocrine tumor, with immunohistochemistry positive for GHRH and negative for prolactin. Her final diagnosis was ectopic acromegaly due to GHRH secreting a lung NET with pituitary somatotroph and lactotroph pituitary hyperplasia and apoplexy in the hyperplastic pituitary.